PENCAHAYAAN KOMBINASI PADA LABORATORIUM TEKNIK ELEKTRO POLITEKNIK NEGERI JAKARTA - Muhamad Ega Alfiana; Muhammad Aji Alfares; Dyah Nurwidyaningrum; Linda Sari Wulandari (Construction and Material Journal, 2020)
Lighting in the Electrical Engineering Laboratory of the Jakarta State Polytechnic (PNJ) is one-factor supporting student practice activities from 07.30 - 16.00 WIB. The observation indicated that the PNJ Electrical Engineering laboratory's lighting undistributed evenly, even though more comprehensive lighting is needed to run well. The purpose of this study is to analyze the suitability of lighting in the Electrical Engineering laboratory with the minimum standard of SNI 03-6575-2001 concerning Procedures for Designing Artificial Lighting Systems in Buildings. The method used in this research is to compare the measurement results against the SNI 03-6575-2001 standard. Researchers took measurements in the Safety and Electrical Machinery laboratory room, Analog laboratory 1 and Digital laboratory 2, Department of Electrical Engineering, State Polytechnic of Jakarta. Analysis of the percentage suitability of combination light in the Safety and Electrical Machinery laboratory in general, namely 70.67%. Based on the measurement results, the suitability of lighting in the Department of Electrical Engineering laboratory, State Polytechnic of Jakarta, is already following SNI's minimum lighting level. Keywords: Electrical Engineering Laboratory, Artificial Lighting, Lighting in The Laboratory.